STUDENTS' ABILITY IN USING INDEPENDENT AND DEPENDENT CLAUSES IN COMPLEX SENTENCES AT SIXTH SEMESTER STUDENTS OF UNIVERSITAS BOSOWA - Osias Tesen Lodan (Teaching English as a Foreign Language Overseas Journal, 2020)
The research is aimed to know the students’ ability in using Independent and Dependent Clauses in Complex Sentences in class VI-A dan VI-B at Bosowa University. The result of this research is expected to give benefits for the readers especially in using Independent and Dependent Clauses in Complex Sentences. This research used descriptive qualitative research. The population of this research is sixth semester students of Bosowa University that have 65 students and the sampling of this research is quota sampling so, in this research the writer takes some of the students in the class which is consist of 30 students from two classes and each class was took 15 students. The result of this research and explanation that the writer got in Bosowa University is 6.6% students got very good category and 20% students got good category while 50% students got enough category and then 23.3 students got poor category. While the mean score of the students is 71.2. It indicates that students sixth semester enough ability in using Independent and dependent clauses in complex sentences.